STATUS OF ADOPTION OF WHEAT (TRITICUM AESTIVUM L.) PRODUCTION TECHNOLOGY IN WHEAT ZONE, RUPANDEHI, NEPAL - Prabin K.; Aavash S.; Rijwan S.; Prajjwol K.; Pratikshya S.; Surakhsya B. (Russian Journal of Agricultural and Socio-Economic Sciences)
Wheat is a staple crop in Nepal, yet significant yield gaps remain. This study aimed to assess the adoption of wheat production technologies in Rupandehi district, specifically in Kotahimai, and Sammarimai rural municipalities. Primary data were collected using a pre-tested interview schedule, supplemented by focus group discussions and key informant surveys. Secondary data were gathered from relevant literature. A total of 85 households were randomly selected for the survey. Data analysis was performed using SPSS and Microsoft Excel, employing descriptive statistics such as mean, standard deviation, frequency, and percentage. A probit regression model was utilized to evaluate the impact of various factors on the adoption of improved wheat varieties, while indexing was used to rank production challenges. The study found that 52% of farmers adopted recommended wheat varieties, while the adoption rates for seed rate, sowing methods, irrigation, and harvesting methods were 39%, 10%, 44%, and 54%, respectively. Significant factors influencing adoption included education level, organizational membership, training participation, subsidies, and loans. Major constraints in wheat production included inadequate irrigation, limited fertilizer availability, lack of agricultural machinery, poor-quality seeds, and pest and disease issues. The probit model results indicated that increased participation in training, organizational membership, higher education levels, and access to subsidies significantly enhance the adoption of improved wheat production technologies.